Expansão do setor sucroenergético no estado de São Paulo e seu impacto em indicadores socioeconômicos - Luz, Yuri Nunes Silva (2021)
A source of food and bioenergy, sugarcane has a strong relevance for the economy of several countries in the tropics and subtropics. In Brazil, the country's history is marked by the influence of sugarcane cultivation, and it is currently the third largest Brazilian crop in planted area. In this sense, this paper studies the impacts of the expansion of the sugar-energy sector on socioeconomic indicators in the state of São Paulo, where the area harvested for sugarcane doubled in a period of ten years, from 2000 to 2010. Using data on agricultural production of sugarcane, territorial areas, and socioeconomic indicators from the 1991, 2000 and 2010 Censuses, the main database of this work consists of a short and balanced panel composed of data from 645 municipalities in the state of São Paulo. Thus, the methodology for linear longitudinal regression models for panel data with a focus on fixed effects is used. Statistically significant and economically substantial effects of the expansion of the harvested area of sugarcane were found on per capita income and for two synthetic indicators of inequality, the Gini index and the Theil-L index. Regarding the IDHM, for the dimensions of longevity and education, the results of the regressions were not very conclusive. As for the income dimension, the coefficients were stable and significant, which is consistent with the other indicators of income and inequality. In addition, the impact of the expansion of the sugar-energy sector on other socioeconomic indicators organized into five categories is also explored: Income and Inequality; Population; Education; Health conditions; and Housing and Infrastructure. These results contribute to an understanding of the broader impacts and effects on social well-being.